2013
DOI: 10.1172/jci71927
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent dominant negative E47 mutation causes agammaglobulinemia and BCR– B cells

Abstract: IntroductionApproximately 85% of patients with early onset of infections, panhypogammaglobulinemia, and less than 2% CD19 + B cells in the peripheral circulation have X-linked agammaglobulinemia (1). This disorder is caused by mutations in Bruton tyrosine kinase (BTK) (2), a cytoplasmic tyrosine kinase that is activated by crosslinking of the pre-B cell and B cell antigen receptors (BCRs) (3). An additional 5%-7% of patients have rare autosomal recessive defects in components of the pre-BCR or BCR or in the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 25 publications
3
65
0
Order By: Relevance
“…S6 and S7, respectively, in the Supplementary Appendix). On the basis of previously reported data, 15 IKAROS protein lacking zinc fingers 1, 2, and 3, as in Family E, behaves similarly to the missense proteins in Families A through D. Because IKAROS functions as a dimer, one might expect these proteins to act in a dominant negative fashion, similar to that recently reported for patients with heterozygous mutations in the DNA-binding domain of E47, 28 another transcription factor required for B-cell development. However, both EMSAs and confocal microscopy showed that the mutant proteins do not inhibit the DNA binding of wild-type IKAROS (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…S6 and S7, respectively, in the Supplementary Appendix). On the basis of previously reported data, 15 IKAROS protein lacking zinc fingers 1, 2, and 3, as in Family E, behaves similarly to the missense proteins in Families A through D. Because IKAROS functions as a dimer, one might expect these proteins to act in a dominant negative fashion, similar to that recently reported for patients with heterozygous mutations in the DNA-binding domain of E47, 28 another transcription factor required for B-cell development. However, both EMSAs and confocal microscopy showed that the mutant proteins do not inhibit the DNA binding of wild-type IKAROS (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…However, a T-cell intrinsic role for NEMO cannot be discounted. The importance of B cells is also evident from studies reporting diminished cTfh frequencies in patients with severe B-cell deficiency due to E47 50 or NFKB2 51 mutations. Our data also shed light on the division of labor between STAT3-activating cytokines in generating cTfh cells, as well as on the functionality and requirements for cTfh subset formation.…”
Section: Discussionmentioning
confidence: 98%
“…These patients may have de novo mutations and WES of the patient and parents’ DNA may reveal a mutation in the patient that is not seen in either parent. Mutations in the transcription factor E47, which is encoded by TCF3 , and in the signal transduction molecule PLCγ2 (encoded by PLCG2 ) were identified in this way [17,18]. It is interesting to note that WES has unmasked the relatively high incidence of autosomal dominant immunodeficiencies.…”
Section: Choosing Immunodeficient Patients For Wesmentioning
confidence: 99%
“…Some of the mutant genes are widely expressed but the phenotype is quite narrow. Examples include STAT1 [25,26], PIK3R1 [4] and TCF3 [17]. Is the protein redundant in other cell lineages?…”
Section: Future Directionsmentioning
confidence: 99%